THE INFLUENCE OF MENTAL ACCOUNTING, STATUS QUO BIAS, REGRET AVERSION BIAS, AND FRAMING EFFECT ON INVESTMENT DECISION-MAKING AMONG GENERATION Z IN SURAKARTA CITY - Aulia, Siti Zhuffara; Achyani, Fatchan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of mental accounting, status quo bias, regret aversion bias, and framing effect on investment decision-making among Generation Z in Surakarta City. The study employs a quantitative approach using primary data collected through the distribution of five-point Likert scale questionnaires to respondents who meet the specified criteria, supported by secondary data from relevant literature. The sampling technique used is purposive sampling, with a total of 140 respondents. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4, through the evaluation of the outer model and inner model. The results indicate that mental accounting, status quo bias, regret aversion bias, and framing effect each have a positive and significant influence on investment decision-making. These findings suggest that psychological factors play an important role in shaping the investment behavior of Generation Z, highlighting that understanding behavioral biases is a crucial aspect in improving the quality of investment decision-making.